Removal of cadmium ions from aqueous solution by using regular MgAICO3 hydrotalcite / Zawati Endut - Endut, Zawati (2008)
Hydrotalcite (MgAlCO3) was found to have ability to exchange anionic species and absorb the cationic species that obtain to remove heavy metal from aqueous system. In this study, Mg/AlCO3 was synthesized by co-precipitation method. Characterization of hydrotalcite by using X-Ray Diffractogram (XRD) showed the presence of sharp peaks which signifying high crystallinity. The presence of sharp peak with d-spacing of 7.95 Å and interlayer spacing of 3.93 Å determined as general features of hydrotalcite. The hydrotalcite composition was investigated by using Fourier Transform Infra Red which showed the presence of broad peak at 3468.39 cm-1 constitutes to hydroxyl group. The peaks at 1382.15 cm-1 and 618.47 cm-1 attribute to carbonate bands and hydrotalcite lattice vibrations (Mg-O-Mg) respectively. The effect of adsorption process was studied by different parameters including contact time, initial concentration and adsorbent dosage. The contact time required 3 hours to obtain the maximum absorption of cadmium was 70.74 %. The percentage of adsorption increased with increasing contact time. For initial concentration, the highest percentage removal was at 60 ppm (67.05 %). The percentage of adsorption decreased with increasing initial concentration. The percentage of adsorption increased with increasing in adsorbent dose.